PENERAPAN RME BERBASIS ICT DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KOMUNIKASI MATEMATIS SISWA DEKADE TERAKHIR: SEBUAH ANALISIS BIBLIOMETRIK - Zogara, Leonard; Daiman, Restiana; Rayu, Ronaldus; Agul, Melania K; Nosi, Yuliana V (UNIKA SANTU PAULUS RUTENG, 2023)
application of the Realistic Mathematics Education (RME) approach supported by Information and Communication Technology (ICT) to improve students' mathematical communication thinking skills in the last decade. Bibliometric analysis will be used to evaluate trends and impact of scientific work on this topic. This research aims to analyze the application of the Realistic Mathematics Education (RME) approach supported by Information and Communication Technology (ICT) in improving students' mathematical communication thinking skills in the last decade. Bibliometric analysis is used to evaluate the trends and impact of scientific works related to this topic. Objective: The aim of this research is to evaluate the contribution of the ICT-based RME approach in improving students' mathematical communication thinking skills in the last decade. In addition, this study also aims to evaluate research trends related to this topic in the last decade. It is hoped that the results of this research can provide useful information for the development of mathematics education in the future.